Activation of peroxymonosulfate by MnO2 with oxygen vacancies: Degradation of organic compounds by electron transfer nonradical mechanism. Issue 3 (June 2022) - Deng, Yuhui; Gao, Peng; Wang, Lu; Zhang, Yongqing; Fu, Juncong; Huang, Renfeng; Zhao, Shuaifei; Wang, Guangzhao; Wei, Yuancheng; Zhou, Shaoqi
Abstract: Recently, ecofriendly and low toxicity manganese-based materials are receiving increased attention for the activation of peroxymonosulfate (PMS). The surface property of manganese-based materials has strong effect on its activation performance. In this study, MnO2 with differing levels of oxygen vacancies (Vo -MnO2 ) were prepared and used for PMS activation. The effects of oxygen vacancies (Vo ), activator dosage, PMS concentration, and the initial pH on para-chloroaniline (PCA) degradation were studied. In these studies, Vo -MnO2 showed good stability and reusability for PMS activation. In addition, a series of experiments revealed the PMS activation mechanism. Interestingly, OH, SO4 - and 1 O2 were not primarily responsible for PCA degradation. PCA was degraded by the reactive complex formed by PMS and Vo -MnO2 . Based on the characterization results and DFT calculations, the introduction of Vo in MnO2 changed the charge distribution of Mn atoms and enhanced PMS adsorption. This is more favorable to form the reactive complex in electron transfer mechanism. Besides, Vo increases the Mn 3+ content in MnO2, which enhances oxidation ability of reactive complex and the efficiency of electron transfer. The degradation efficiency of pollutants in the Vo -MnO2 /PMS system has been improved significantly. This study highlights the pivotal roles of Vo in electron transfer mechanism and provides a new method for the practical application in wastewater treatment. Graphical Abstract: ga1 Highlights: OH, SO4 - and 1 O2 were not primarily responsible for PCA degradation. PCA degradation occurred by the electron transfer mechanism in the Vo -MnO2 /PMS system. Vo enhanced the PMS adsorption on the MnO2 surface and thus facilitated PCA degradation. Vo increased the Mn 3+ content, thereby promoting the electron transfer process. Vo -MnO2 was very stable during the reaction process and could be reused.